Micro-pouvoirs en action au doctorat : la perception des étudiants - Annick Vallières; Nataly Levesque; Julie Bernard (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Drawing on the doctoral environment literature, this research points to the micro-powers of the academic system and their consequences on doctoral students. Through a Foucauldian lens, the study's objective is to provide a better understanding of doctoral students' perceptions of their postgraduate experience and thus propose mentoring and support practices that reflect their real needs. For this study, 11 semi-structured interviews were conducted. Subsequently, the research team processed to a inductive analysis to identify the central themes, including doctoral supervision, doctoral program requirements, and standardization of sacrifices. The originality of this study lies in the theoretical angle privileging doctoral students' accounts of their own doctoral experiences and recommendations for fostering a more humane academic experience. The main results of this study lead us to a compromise between the sacrifices imposed in exchange for the social approval of the different actors of the academic institution. Finally, avenues for future research are proposed as well as the pedagogical implications arising from it are discussed.